Influence of leadership competencies on transport infrastructure projects' success: A mediated moderation through innovative-work-behavior and the project type - Abdul Ghaffar Rana; Aleena Shuja (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
This paper intends to examine the influence of competencies of project leaders on success of transport infrastructure development projects. Subsequently, to decide on intervening role of innovative-work-behavior on project success. Lastly, investigating contingent effect of project type as moderator in objectifying the impact of innovative-work-behavior on project success. In order to justify key ambitions of intended study, the constructs were measured using a questionnaire-based survey from transport infrastructure development departments of Lahore, Pakistan. Validation of theoretical model was confirmed by means of structural equation modeling using Amos. Study findings suggest that innovative-workbehavior of project employees completely mediates effect incurred by leadership competencies on project success. Likewise project type with respect to strategic importance, contract type, application area and complexity moderates the relationship concerning innovative-work-behavior and project success. This study accounts for practical findings benefiting project managers in capitalizing on their leadership capabilities and promoting innovation within their teams for successfully accomplishing transport infrastructure projects. The novelty of this research lies in the fact that through taking maximum advantage of its empirical endorsement for achieving project success through development and enactment of certain key leadership competencies of project managers will encourage innovative actions of employees based on diverse project characteristics.
Keywords: 330; Pakistan; transport infrastructure; leadership competencies; project type; innovative-work-behavior; project success